Forest malaria and prospects for anti-malarial chemoprophylaxis among forest goers: findings from a qualitative study in Lao PDR - Jongdeepaisal, M; Inthasone, S; Khonputsa, P; Malaphone, V; Pongsoipetch, K; Pongvongsa, T; Mayxay, M; Chindavongsa, K; Pell, C; Maude, RJ (BioMed Central, 2022)
Background Despite significant decline in malarial incidence and mortality in countries across the Greater Mekong Subregion, the disease remains a public health challenge in the region; transmission continues mainly among people who visit forests in remote areas, often along international borders, where access to primary healthcare is limited. In the absence of effective vector-control measures and limited exposure periods, malaria chemoprophylaxis has been proposed as a strategy to protect forest goers. As a rarely used approach for indigenous populations, questions remain about its feasibility and acceptability. Drawing on in-depth interviews with forest goers and stakeholders, this article examines opportunities and challenges for implementation of anti-malarial chemoprophylaxis for forest goers in Lao PDR. Methods In-depth interviews were conducted with 16 forest goers and 15 stakeholders in Savannakhet province, Lao PDR. Interview topics included experience of malaria prevention and health services, and perceptions of prophylaxis as a potential component of malaria elimination strategy. The interviews were transcribed and coded using inductive and deductive approaches for qualitative thematic analysis. Results In ethnically and geographically diverse villages, awareness of malaria risk prompts forest goers to protect themselves, albeit sub-optimally using available preventive measures. Stakeholders highlighted challenges for targeting at-risk populations and approaches to address forest malaria in southern Lao PDR. Among policymakers, choice and cost of anti-malarials, particularly their efficacy and source of funding, were key considerations for the feasibility of malaria prophylaxis. Acceptability of prophylaxis among forest goers was also influenced by the complexity of the regimen, including the number of tablets and timing of doses. Implementation of prophylaxis may be affected by a lack of transportation and communication barriers in remote communities. Conclusion Adding prophylaxis to existing malaria control activities requires strengthening the capacity of local health workers in Lao PDR. Ideally, this would be part of an integrated approach that includes strategies to address the other febrile illnesses that forest goers describe as priority health concerns. The prophylactic regimen also requires careful consideration in terms of effectiveness and simplicity of dosing.